2019
DOI: 10.1186/s12957-019-1638-0
|View full text |Cite
|
Sign up to set email alerts
|

Which papillary thyroid microcarcinoma should be treated as “true cancer” and which as “precancer”?

Abstract: Background Papillary thyroid microcarcinoma (PTMC) generally is a cancer with excellent prognosis, but the term “cancer” sounds severe and harsh, which can elicit emotional and physical responses from patients. To eliminate the word “cancer,” the term noninvasive follicular thyroid neoplasm with papillary-like nuclear features (NIFTP) was introduced. However, not all PTMCs can be classified as NIFTP. Sometimes, very aggressive PTMC cases might be observed. Some authors suggest that one of the risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 39 publications
2
25
0
Order By: Relevance
“…Next, we analyzed demographic and ultrasound features and compared them with histopathological characteristics. Some of them are considered pathognomonic for aggressive PTMC entities [ 9 ]. Univariate and multivariate logistic regression analyses were used to determine the relationships of demographic and ultrasound features with histopathological characteristics such as minETE, capsular and vascular invasion and LNM.…”
Section: Methodsmentioning
confidence: 99%
“…Next, we analyzed demographic and ultrasound features and compared them with histopathological characteristics. Some of them are considered pathognomonic for aggressive PTMC entities [ 9 ]. Univariate and multivariate logistic regression analyses were used to determine the relationships of demographic and ultrasound features with histopathological characteristics such as minETE, capsular and vascular invasion and LNM.…”
Section: Methodsmentioning
confidence: 99%
“…General practitioners' easy access to some high-quality imaging tests in their practices may also be responsible for this situation. Additionally, in Poland, we also observed that easy access to healthcare, such as additional private insurance, increases the rate of new diagnoses of small PTC tumors [8].…”
Section: Plos Onementioning
confidence: 68%
“…The next argument for the overdiagnosis and overtreatment of PTC is its very low recurrence rate after surgery [8]. In this study, we estimated that none of CSA-yes patients in whom PTC was diagnosed after surgery showed any signs of disease recurrence, while 17.8% of patients diagnosed with PTC based on clinical symptoms showed signs of TC recurrence.…”
Section: Plos Onementioning
confidence: 86%
See 2 more Smart Citations